2017
DOI: 10.1021/acsami.7b01260
|View full text |Cite
|
Sign up to set email alerts
|

Galvanostatic Rejuvenation of Electrochromic WO3 Thin Films: Ion Trapping and Detrapping Observed by Optical Measurements and by Time-of-Flight Secondary Ion Mass Spectrometry

Abstract: Electrochromic (EC) smart windows are able to decrease our energy footprint while enhancing indoor comfort and convenience. However, the limited durability of these windows, as well as their cost, result in hampered market introduction. Here, we investigate thin films of the most widely studied EC material, WO. Specifically, we combine optical measurements (using spectrophotometry in conjunction with variable-angle spectroscopic ellipsometry) with time-of-flight secondary ion mass spectrometry and atomic force… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 16 publications
(35 reference statements)
2
38
1
Order By: Relevance
“…The above results suggest strongly that Li ion de-trapping is possible, and conclusive evidence on this matter was obtained by analyzing the Li content-including its depth profile-by time-of-flight elastic recoil detection analysis (ToF-ERDA) [165] and time-offlight secondary ion mass spectroscopy (ToF-SIMS) [166]. Fig.…”
Section: Rejuvenation Of Degraded Ec Filmsmentioning
confidence: 75%
“…The above results suggest strongly that Li ion de-trapping is possible, and conclusive evidence on this matter was obtained by analyzing the Li content-including its depth profile-by time-of-flight elastic recoil detection analysis (ToF-ERDA) [165] and time-offlight secondary ion mass spectroscopy (ToF-SIMS) [166]. Fig.…”
Section: Rejuvenation Of Degraded Ec Filmsmentioning
confidence: 75%
“…12,13 Nevertheless, there has remained an urgent need for other means to extend device longevity, and it was recently shown that electrochemical treatments can rejuvenate degraded EC films and restore their original properties. This work was initiated with WO 3 films [14][15][16][17][18] and was later extended to films of MoO 3 19 and TiO 2 . 20 These oxides are cathodic and similar in many ways, and it is commonly accepted that their electrochromism is associated with the intercalation/deintercalation of small cations (H + or Li + ) and concurrent insertion/extraction of electrons.…”
mentioning
confidence: 99%
“…Rejuvenation of WO 3 has been firmly related to electrically induced extraction of trapped Li + ions from degraded films. 14,15,18 However, the situation is more complex for the case of anodically coloring nickel oxide in the Li + -based electrolytes. [21][22][23] Its coloration mechanism remains contentious and even the ionic species involved in the EC process are controversial, furthermore, the physical and chemical origins of the films' irreversibility remain obscure, experimentally as well as theoretically.…”
mentioning
confidence: 99%
“…Sung et al 13 also reported an improvement in the durability with an inorganic protective layer for the laminated device V 2 O 5 /WO 3 , but organic electrolytes rather than inorganic ones were used for device lamination. Baloukas et al 14 have demonstrated ion trapping and detrapping limited in single EC layer WO 3 films.…”
Section: Structural/microstructure Characterization Of Device Degradamentioning
confidence: 99%